The Influence of Perceived Usefulness and Perceived Ease of Use within The Regional Government Information System (SIPD) on Regional Financial Management System - Rotinsulu, Paula; Karamoy, Herman; Warongan, Jessy D. L. (Syntax Literate, 2024)
This research is motivated by one of the factors in realizing good governance as a system that has been published by the government, namely SPBE to utilize Information Technology as a means of realizing good governance. SIPD is part of SPBE which is designed as an internal local government system for financial management so that this information can provide effective benefits in decision making. The problem is that the system can run well if its users accept and understand it well. Factors that influence the increase in its use is the acceptance of each individual who becomes a user. This study aims to determine the effect of Perceived Usefulness and Perceived Ease of Use (perceived ease of use) of Regional Government Information Systems (SIPD) on the Application of Regional Financial Management Systems in North Minahasa Regency. The approach used is quantitative with this type of correlational research. Data collection using a questionnaire. Data analysis technique using multiple regression. The results of this study can be concluded that the Perceived Usefulness of SIPD has a positive and significant effect on the application of the regional financial management system in North Minahasa Regency with a coefficient of determination of 53.90%. Perceived Ease of Use (perceived ease of use) SIPD has a positive and significant effect on the application of regional financial management systems in North Minahasa Regency with a coefficient of determination of 18.60%.